Comparação dos valores de recuperação da frequência cardíaca e do índice cronotrópico após teste de Bruce em esteira em mulheres idosas obesas com alta e baixa força muscular - Silva, Cristiane Rocha da (2018)
The aim of the present study was to analyse heart rate recovery (HRR) and chronotropic index (CI) after treadmill Bruce test in obese elderly women classified on the basis of relative manual grip strength. Methods: Eighty-eight obese elderly women who were between the ages of 60 and 87 participated in the study and were categorized and enrolled to one of two groups based on lower (< 1.51 m²) or higher (≥ 1.51 m²) relative handgrip strength, respectively. The heart rate recovery in the first and second minutes following the treadmill exercise test and the chronotropic index were compared between groups. Results: The higher relative handgrip strength group presented a significantly higher peak heart rate (p= 0,019) during exercise and a faster HRR at the first (p = 0.003) and second minutes (p = 0.002) after the ergometric test compared to the low manual grip strength group (p=0,001). Furthermore, there was a tendency (p = 0.059) towards a significantly higher CI, six-minute walk test (p = 0.001) and low time up and go time in the group of high relative manual grip strength compared to the low force group. Conclusion: In conclusion, elderly women with greater relative handgrip strength also demonstrated a better heart rate response during and following exercise and tendency to higher chronotropic index, possibly indicating better autonomic balance.